Crux of the problems and the teaching of Private International Law. Selected cases - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This paper is a reflection on the use of problem nodes in the teaching of private international law today. The clear, direct and simple exposition of the most relevant problematic issues of private international law makes the understanding of the subject better for the students. In this work a selection is made of some of the problem nodes that are transmitted in the classroom. The exposition and solution of them manages to attract and motivate the students, and also manages to enhance their capacity for legal argumentation. Offering the teacher a practical vision of the just solutions achieved byapplying the rules of private international law.